Change of Cells and Layers Sizes of Hemp (Cannabis sativa L.) Bast Fibers in the Synthetic Breeding Process - Mishchenko, Serhii (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The sizes (length and width) of cells and layers of primary and secondary bast fibers of hemp (Cannabis sativa L.) were reduced due to self-pollination (the phenomenon of inbred depression). The average length of the primary bast fibers cells decreased from 66.15 to 60.45 µm and cell width decreased from 40.05 to 36.30 µm. The average length of the secondary bast fibers cells decreased from 26.55 to 21.75 μm and cell width decreased from 15.75 to 14.25 μm. The values of these anatomical characteristics have increased as a result of free pollination and hybridization of inbred lines and the creation of a synthetic population (the phenomenon of heterosis). The sizes of the primary bast fibers cells in synthetic population plants were 73.95 × 47.40 μm and the sizes of the secondary bast fibers cells was 32.70 × 22.05 μm. The thickness of the primary fiber layer in the Hlukhivsky 58 variety was 230.25, inbred lines were 155.25, and the synthetic population was 264.00 μm. The thickness of the second fiber layer was 99.75, 77.25 and 116.75 μm, the total thickness of the fiber layer was 330.00, 232.50 and 380.75 μm, respectively. The proposed method for the creation of synthetic populations of monoecious hemp by the scheme "variety – inbred lines – synthetic population" is effective at increasing the fiber content of plants.